Co3O4-loaded ZnO nanofibers for excellent hydrogen sensing. (18th October 2019) - Lee, Jae-Hyoung; Kim, Jin-Young; Kim, Jae-Hun; Mirzaei, Ali; Kim, Hyoun Woo; Kim, Sang Sub
Abstract: The development of outstanding H2 -sensing materials is vital for the realization of ecofriendly devices using H2 -based energy. ZnO nanofibers have excellent H2 -sensing performance. In this study, we synthesized a series of Co3 O4 -loaded ZnO nanofibers with the formula (1-x)ZnO-xCo3 O4 (x = 0.03, 0.05, 0.1, and 0.15, representing the molar ratio of Co3 O4 ) via electrospinning to improve the H2 -sensing properties of pristine nanofibers. The sensing results indicated that a sensor with a nominal composition of 0.95ZnO-0.05Co3 O4 had the highest response of 133 to 10 ppm H2 gas, with good H2 selectivity. The main mechanisms underlying the excellent H2 -sensing capability of the optimized gas sensor involved ZnO surface/grain boundaries and Co3 O4 . Graphical abstract: Change of potential barriers at ZnO/ZnO homointerfaces in the H2 atmospheres, energy levels of ZnO and Co3 O4 after intimate contact, and responses of Co3 O4 loaded ZnO to H2, CO, NO2 gases.Image 1 Highlights: The n - p ZnO–Co3 O4 composite nanofibers showed higher H2 sensing response, superior to that of pristine n –ZnO nanofibers. The composite nanofibers with composition of 0.95 ZnO-0.05 Co3 O4 showed the highest response to H2 at 300 °C. H2 sensing was related to the H2 -induced reduction of resistance in ZnO and formation p-Co3 O4 /n-ZnO heterojunctions.